Agroecological Living Landscapes: A Context Assessment in Murewa, Zimbabwe - Chimonyo, Vimbayi G. P.; Sibanda, Telma; Choruma, Dennis J.; Falconnier, Gatien N.; Baudron, Fréderic (CGIAR, 2023)
This report contributes to Output 2.1. Baseline – current conditions of agricultural systems of smallholder farmers in the identified Agroecological Living Landscape (ALL) and provides context to their current state. Therefore, the document is a Context Assessment report that is developed and maintained to ensure a thorough understanding of the operational context as well as that of the stakeholders and communities. This document is a living document and will continuously evolve. For Zimbabwe, the ALLs are at the district level, with two sub-ALLs at the ward level. The current Context Assessment is reported for Murewa, which is at the district level, and, where information is available, the wards where the nuclei ALLs have been established were given. We used gray literature from published articles, reports, and web pages as the main source of information. This information was validated with data collected during focus group discussions (FGDs), key informant interviews (KIIs), and meetings. The key findings show that Murewa comprises mainly family farmers characterized as being resource-poor. The community is largely patriarchal, with chiefs and herdmen managing natural resources. The main production constraints include, but are not limited to, weather risks (droughts and floods) and low access to improved technologies. Many farmers participate in market gardening and produce tomatoes, onions, butternut, and cabbages. Their proximity to Harare, the capital city of Zimbabwe, improves access to markets, but the lack of proper postharvest handling decreases profits. Maize, groundnut, and sweet potatoes are the main field crops produced while farmers keep cattle, goats, pigs, and poultry. The main environmental hazards are soil erosion, gullies, and deforestation. Communities in Murewa have good access to diverse foods across the different food groups, most of which are sourced from home gardens. However, better food availability occurs from February to September, while the peak lean period is experienced by communities in January and from October to December. Findings from KIIs and FGDs across Murewa District revealed that several farmer groups and committees have been formed. Farmer groups are small and formed on their own initiative or through development agencies with specific objectives, such as strengthening food security and improving household income of group members. Many of the groups formed are not concerned about diversity but rather making a contribution to the group cause.